A travel time‐based approach to model kinetic sorption in highly heterogeneous porous media via reactive hydrofacies. Issue 12 (7th December 2016) - Finkel, Michael; Grathwohl, Peter; Cirpka, Olaf A.
Abstract: We present a semianalytical model for the transport of solutes being subject to sorption in porous aquifers. We couple a travel time‐based model of advective transport with a spherical diffusion model of kinetic sorption in nonuniform material mixtures. The model is formulated in the Laplace domain and transformed to the time domain by numerical inversion. By this, three‐dimensional transport of solutes undergoing mass transfer between aqueous and solid phases can be simulated very efficiently. The model addresses both hydraulic and reactive heterogeneity of porous aquifers by means of hydrofacies, which function as homogeneous but nonuniform subunits. The total exposure time to each of these subunits controls the magnitude of sorption effects, whereas the particular sequence of facies through which the solute passes is irrelevant. We apply the model to simulate the transport of phenanthrene in a fluvio‐glacial aquifer, for which the hydrofacies distribution is known at high resolution, the lithological composition of each facies has been analyzed, and sorption properties of the lithological components are available. Taking the fully resolved hydrofacies model as reference, we evaluate different approximations referring to lower information levels, reflecting shortcomings in typical modeling projects. The most important feature for a good description of both the main breakthrough and tailing of phenanthrene is the nonuniformity of the porous medium. While spatial heterogeneity of chemical properties might be neglected without introducing a large error, an approximation of the facies' composition in terms of a uniform substitute material considerably compromises the quality of the modeling result. Key Points: Efficient semianalytical transport model for sorbing solutes in heterogeneous porous media Hydraulic and reactive heterogeneity are considered by spatially distributed nonuniform hydrofacies Results show major significance of facies nonuniformity to accuracy of simulated solute breakthrough